KESEMPATAN KERJA DAN PENDAPATAN: MIGRASI PENDUDUK INDRAMAYU SEBAGAI TKI DI TAIWAN - Afra Aldilawulandari Annika Bharata (Yayasan Literasi Sains Indonesia, 2024)
Indramayu, particularly in its district, faces the challenge of poverty, with a poverty rate of 14.29%. The percentage of the population living in poverty reaches 16.28%. In response to this situation, many residents of Indramayu choose to become overseas Indonesian workers (TKI) in Taiwan as a means to improve their families’ well-being. This study aims to understand employment opportunities and income earned by Indramayu migrants working in Taiwan. The research employs a literature review approach with a qualitative descriptive method. Findings reveal that the primary driver of international migration is the prospect of high-income employment. Migrants aspire to enhance their standard of living and secure better earnings. Additionally, the presence of relatives who have already migrated or settled in Taiwan serves as an attractive factor. While the direct physical impact on village development may not be immediately visible, significant social changes occur. Family education levels improve, new job opportunities emerge, and lifestyle shifts lead to an overall enhancement in quality of life. In summary, the migration of TKI workers from Indramayu to Taiwan has multifaceted implications for both societies.